PROBLEMS OF ORGANIZING EDUCATIONAL AND ORGANIZATIONAL MANAGEMENT ACTIVITIES IN NON-GOVERNMENTAL HIGHER EDUCATION INSTITUTIONS - Khojibokieva, Nigina (Science technology&Digital finance, 2023)
Detailed information is given about the entry of non-state higher education institutions into our country and the problems arising in its establishment. Issues of private and non-state higher education market, its development, formation of honest and healthy competition, increasing the quality of education of universities that sell diplomas without providing education, training of qualified personnel, ensuring social justice in society, correct formation of the labor market, work of talented students in decent working conditions, decent special attention is paid to creating opportunities for employment, forming the same approach and vision towards public and private higher education institutions.